2005
DOI: 10.1212/01.wnl.0000179303.72345.ce
|View full text |Cite
|
Sign up to set email alerts
|

The nature and frequency of cognitive deficits in children with neurofibromatosis type 1

Abstract: There is an extremely high frequency of cognitive problems in children with neurofibromatosis type 1, making cognitive dysfunction the most common complication to affect quality of life in these children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

53
641
5
22

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 541 publications
(744 citation statements)
references
References 40 publications
53
641
5
22
Order By: Relevance
“…However, the disorder is highly variable in terms of clinical presentation, with only a minority of children experiencing significant physical complications (Huson et al 1989). In contrast, cognitive dysfunction is wide ranging, affecting approximately 80 % of children with NF1 in one capacity or another (Hyman et al 2005;Hyman et al 2006).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…However, the disorder is highly variable in terms of clinical presentation, with only a minority of children experiencing significant physical complications (Huson et al 1989). In contrast, cognitive dysfunction is wide ranging, affecting approximately 80 % of children with NF1 in one capacity or another (Hyman et al 2005;Hyman et al 2006).…”
mentioning
confidence: 99%
“…Beyond intellect, studies have found specific deficits in visual perception, most consistently on the Benton Judgment of Line Orientation (JLO) task (Rowbotham et al 2009;Hyman et al 2005;Schrimsher et al 2003;Benton et al 1983), along with more generalized difficulties in the areas of language development (Hyman et al 2005), executive functioning (Templer et al 2012;Roy et al 2010;North et al 2002), and attention (Templer et al 2012;North et al 2002). Understanding of these deficits has helped to guide intervention trials and clinical practice with the NF1 population, shaping assessment and intervention practices.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Additional physical symptoms include freckling of the groin and/or underarm, Lisch nodules of the iris, optic pathway gliomas, and bone lesions [62]. Approximately 80% of individuals with NF1 exhibit deficits in cognitive functioning [63]. Poor social skills, signs of attention deficit hyperactivity disorder (ADHD), and difficulties with executive function are also observed in affected individuals.…”
Section: Neurofibromatosis Typementioning
confidence: 99%
“…Learning disabilities occur in at least 50% of children with NF1, making cognitive problems the most common complication to affect the quality of life in this group (Hyman et al, 2005). Attention‐deficit/hyperactivity disorder (ADHD), autism spectrum disorder (ASD), and sleep disturbance are also highly prevalent (Hyman et al, 2006; Leschziner et al, 2013; Morris et al, 2016) and can persist throughout life (Constantino et al, 2015; Descheemaeker et al, 2013; Mautner et al, 2015; van Eeghen AM et al, 2013).…”
Section: Introductionmentioning
confidence: 99%